Radionuclide Imaging of Atherothrombotic Diseases - Stacy, Mitchel R. (Curr Cardiovasc Imaging Rep, 2019)
PURPOSE OF REVIEW: A variety of approaches and molecular targets have emerged in recent years for radionuclide-based imaging of atherosclerosis and vulnerable plaque using single photon emission computed tomography (SPECT) and positron emission tomography (PET), with numerous methods focused on characterizing the mechanisms underlying plaque progression and rupture. This review highlights the ongoing developments in both the preclinical and clinical environment for radionuclide imaging of atherosclerosis and atherothrombosis. RECENT FINDINGS: Numerous physiological processes responsible for the evolution of high-risk atherosclerotic plaque, such as inflammation, thrombosis, angiogenesis, and microcalcification, have been shown to be feasible targets for SPECT and PET imaging. For each physiological process, specific molecular markers have been identified that allow for sensitive non-invasive detection and characterization of atherosclerotic plaque. SUMMARY: The capabilities of SPECT and PET imaging continue to evolve for physiological evaluation of atherosclerosis. This review summarizes the latest developments related to radionuclide imaging of atherothrombotic diseases.